(untitled) (Eurasian Research Bulletin, 2023)
An analysis of the world economic trends in capital construction, in particular in the production of binding materials and cement, shows that the use of resources and energy-saving, innovative technologies is a requirement of the present and future. The article presents ideas and experimental developments of energy-saving nanotechnologies, innovative methods for obtaining astringent low water requirements.